Implementasi Experiential Learning pada Materi Energi dan Perubahannya - Salsabila, Ainus; Agustin, Zulfani Nurdiana (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
Experiential learning can help the learning process and provide a unique touch in the learning process. The application of experiential leaning models using self-created and designed learning media can help students in finding concepts independently. This research uses two types of media, namely simple props and PhET simulations, so it is hoped that students can learn according to the framework of experiential learning by finding their own concepts based on experience. This research uses a type of design research (Design Based Research), which aims to solve a complex problem and develop knowledge about a characteristic of the related product, using a semi-qualitative approach. This study involved 23 students of class VII of SMP Negeri in Pademawu, Pamekasan. Data collection techniques in this study used observation and surveys. The results of data analysis showed that the use of simple props received a good response from students and received a very decent response from validators. Keywords: experiential learning, learning process, teaching aid